Implementasi Nilai-Nilai Pancasila dalam Menangkal Pengaruh Pergaulan Bebas terhadap Kesehatan di SDN Sempol 1 - Ahmad Dhavi Santoso; Cecilia Sabatini; Muhammad Nurul Yaqin; Yusril Ihza Alizain; Fauzi Ahmad Zarkasi; Muhammad Raditya; Fieans Althaf Alfarabi; Agung Nugroho Puspito; Dimas B. Zahrosa (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
This study aims to analyze the application of Pancasila values in the era of globalization, improve adolescents' understanding of the dangers of drugs and free sex, and examine the quality of health services within the National Health Insurance Program (JKN). Globalization has brought negative consequences including the erosion of Pancasila values, rising drug abuse, promiscuity among adolescents, and uneven healthcare service quality. This research employed a literature review and a retrospective observational approach through a systematic review using meta-synthesis techniques, supplemented by a counseling program for 50 adolescents in Simpang 1 Village on July 22, 2023. Respondents' understanding rose from 58% before the session to 86% afterward. Chi-Square test results showed p < 0.05, indicating a significant relationship between service quality and patient satisfaction among JKN participants, with service speed, healthcare worker friendliness, and facility conditions as the primary determinants. Strengthening Pancasila values through adolescent education and improving healthcare service quality are two mutually reinforcing strategies for addressing globalization's pressures. These findings are expected to serve as a reference for the government, educators, and healthcare professionals in designing more effective character-building and public service programs.